Spatial Distribution of Ticks (Arachniada: Argasidae and Ixodidae) and Their Infection Rate to Crimean-Congo Hemorrhagic Fever Virus in Iran - Ahmad Ali Hanafi-Bojd; Samin Jafari; Zakkyeh Telmadarraiy; Abbas Abbasi-Ghahramanloo; Eslam Moradi-Asl (Tehran University of Medical Sciences, 2021)
Background: The Crimean-Congo Hemorrhagic Fever (CCHF) is one of the most important arthropod-borne viral diseases with a mortality rate of about 30% among humans. The disease, caused by a Nairovirus, is transmitted to humans and animals by hard and soft ticks. This study aimed to determine the distribution of soft and hard ticks in the past three decades in Iran with an emphasis on the vectors of the CCHF virus. Methods: In this review, all studies that were carried out in different regions of Iran from 1979 to 2018 and their results were published in prestigious journals were used to create a database. The distribution of ticks was mapped using ArcMap10.3. Results: Based on the results, nine genera and 37 species of soft and hard ticks were recorded in Iran. So far, six genera and 16 species of hard and soft ticks were reported to be infected with the CCHF virus. The infection to this virus was reported from 18 out of 31 provinces, with a high rate in Sistan and Baluchistan as well as Khuzestan provinces. The highest levels of CCHF infection belonged to Hyalomma marginatum and H. anatolicum. Conclusion: The main vectors of CCHF, H. marginatum and H. anatolicum, were reported in more than 38.7% of Iran's provinces, and these two species were identified as invasive species in Iran. Thus, control activities should be strengthened to avoid the outbreaks of CCHF.